Production process of bend-resistant copper foil for high-safety lithium battery

CN122833667APending Publication Date: 2026-09-29JIAYUAN TECH (NINGDE) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611170468.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

然而,对于厚度在5-8μm的超薄铜箔而言,常规添加剂体系难以兼顾晶粒细化和内应力消除,所制铜箔往往存在晶粒粗大、针孔缺陷多、抗拉强度与延伸率不足、耐弯折性能差等问题

Benefits of technology

[0022]1、本发明通过十二烷酸与1,2-二氨基苯在二甲苯中经高温反应,生成含苯并咪唑环的中间体;然后将中间体与环氧氯丙烷在碱性条件下反应开环,再与丙烯酰氯相互作用引入可参与光接枝的碳碳双键及长链烷基、苯并咪唑结构,即得中间体。然后以中间体、环氧氯丙烷及丙烯酰氯等为原料,通过化学反应制得改性剂。在氮气气氛下,将巯基聚乙二醇氨基分散于乙醇中,加入引发剂和改性剂,在引发剂及紫外光照射下改性剂与巯基聚乙二醇氨基发生巯基-烯点击化学反应,使改性剂通过共价键接枝到巯基聚乙二醇氨基的链段上,最终制得功效添加剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to copper foil production technology field, specifically for a kind of high security lithium battery with production process of bending-resistant copper foil;The production process of high security lithium battery with bending-resistant copper foil includes the following steps: high-purity copper wire is dissolved in dilute sulfuric acid to prepare electrolyte, control copper ion, sulfuric acid and chloride ion concentration;Electrolyte is transported to high tank, and specific composite additive is added in proportion to carry out electrodeposition to prepare green foil;Green foil is pickled, washed, then soaked in antioxidant liquid containing glucose, benzotriazole and silane coupling agent, finally squeezed, dried, wound and cut, to obtain copper foil;The copper foil produced by the present application has excellent bending resistance, high elongation and oxidation resistance, which can effectively inhibit the fracture of lithium battery pole piece and the shedding of active material during charging and discharging process, significantly improve the cycle life and safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of copper foil production technology, specifically to a production process for high-safety, bend-resistant copper foil for lithium batteries. Background Technology

[0002] With the rapid development of new energy vehicles, portable electronic devices, and energy storage systems, increasingly higher demands are being placed on the energy density, cycle life, and safety of lithium-ion batteries. Copper foil, as the negative electrode current collector in lithium batteries, directly affects the battery's charge-discharge efficiency, internal resistance, heat distribution, and cycle stability. In recent years, in particular, high-energy-density battery designs have tended to use thinner copper foil (≤8μm) and higher areal capacity negative electrodes. This causes the copper foil to be repeatedly subjected to mechanical stress (such as winding and electrode expansion and contraction) during battery manufacturing and charge-discharge processes, making it highly susceptible to breakage, wrinkling, or active material shedding, becoming one of the key bottlenecks limiting battery safety and lifespan.

[0003] Existing technologies for producing electrolytic copper foil typically employ a copper-sulfuric acid electrodeposition process, adding conventional additives such as gelatin, sodium polydipropane sulfonate (SPS), and hydroxyethyl cellulose to control the crystal orientation and surface roughness of the copper foil. However, for ultra-thin copper foils with a thickness of 5-8 μm, conventional additive systems struggle to simultaneously achieve grain refinement and internal stress relief, often resulting in copper foils with coarse grains, numerous pinhole defects, insufficient tensile strength and elongation, and poor bending resistance. Furthermore, ultra-thin copper foils are highly susceptible to oxidation and discoloration in air. The oxide layer not only reduces weldability and conductivity but also weakens the bonding strength with the negative electrode active material, further deteriorating battery performance. Therefore, this invention provides a production process for high-safety, bend-resistant copper foil for lithium batteries to address the aforementioned technical problems! Summary of the Invention

[0004] The purpose of this invention is to provide a production process for high-safety, bend-resistant copper foil for lithium batteries. The copper foil produced has excellent bend resistance, high elongation, and oxidation resistance, which can effectively suppress electrode breakage and active material shedding during the charging and discharging process of lithium batteries, and significantly improve the cycle life and safety of the battery.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A manufacturing process for bend-resistant copper foil for high-safety lithium batteries includes the following steps:

[0007] Step 1: Add copper wire with a purity of ≥99.99% to a copper dissolving tank, add water and dilute sulfuric acid, and bubble air in to dissolve the copper. After adjusting the copper ion content, sulfuric acid concentration, chloride ion content and temperature in the solution, an electrolyte is obtained.

[0008] Step 2: The electrolyte obtained in Step 1 is transported to a high-level tank, and additives are added to the high-level tank at a dosage ratio of 4-6 L / h. After mixing evenly, the electrolyte containing additives is transported to the electrolytic cell through the inlet pipe of the foil-making machine for electrodeposition to obtain the foil. The dosage of additives in each cubic meter of electrolyte is 0.3-0.6 L.

[0009] Step 3: The obtained raw foil is acid-washed with electrolyte and rinsed with pure water, then dried. The cleaned copper foil is then immersed in an antioxidant solution at 30-40℃ for 10-20 seconds. It is then squeezed dry by extrusion rollers, dried, wound up and slit to obtain a high-safety, bend-resistant copper foil for lithium batteries with a thickness of 5-8μm. The drying temperature is 120-130℃.

[0010] Furthermore, the electrolyte contains 90-120 g / L of copper ions, 100-130 g / L of H2SO4, and 20-30 ppm of chloride ions, and the temperature of the electrolyte is set to 45-55°C.

[0011] Furthermore, the electrodeposition temperature was set to 45-65℃, and the current density was set to 60-80 A / dm³. 2 The electrolyte flow rate is set to 35-45 m³ / h. 3 / h.

[0012] Furthermore, the specific composition of the additive is as follows: 0.5-1.0 g / L of bis(benzenesulfonyl)imide, 6-10 g / L of gelatin, 0.2-0.3 g / L of polyethylene glycol, 2-5 g / L of functional additive, 0.5-0.8 g / L of dextrin, 2-5 g / L of 3,4-dioxomethylenebenzaldehyde, and 2-5 g / L of sodium 3-mercapto-1-propanesulfonate; and the molecular weight of the gelatin is 10,000-20,000; the molecular weight of the polyethylene glycol is 3,000-5,000.

[0013] Furthermore, the preparation method of the aforementioned functional additive is as follows: under a nitrogen atmosphere, mercaptopolyethylene glycol amino is uniformly dispersed in ethanol, and after heating to 60-70°C, an initiator and a modifier with a mass of 0.5-0.7 times that of mercaptopolyethylene glycol amino are added. The mixture is then subjected to a temperature of 40-50°C and a light intensity of 80-120 mw / cm². 2 Under certain conditions, the mixture is irradiated with ultraviolet light at a wavelength of 365nm for 2-3 hours, and then the ethanol is distilled off under reduced pressure to obtain the functional additive.

[0014] Furthermore, the initiator is any one of azobisisobutyronitrile, azobisisobutyronitrile, and dimethyl azobisisobutyrate, and its amount is 1-5 wt% of the total mass of mercaptopolyethylene glycol amino and modifier.

[0015] Furthermore, the method for preparing the modifier is as follows:

[0016] Step 1: Under nitrogen protection, dodecanoic acid, 1,2-diaminobenzene and xylene are mixed at a ratio of 1 mol:(1-1.5) mol:2-5 L. The mixture is first kept at 155-160℃ for 4-6 h, and then at 215-220℃ for 3-4 h. The reaction solution is then cooled and distilled under reduced pressure. The resulting intermediate is stored for later use.

[0017] Step 2: At 55-60℃, add the intermediate to dimethyl sulfoxide at a dosage ratio of 2-4 mol / L, and add sodium hydroxide in an equimolar amount with dodecanoic acid. Mix and stir at a speed of 200-400 r / min for 40-60 min, then add epichlorohydrin in an equimolar amount with sodium hydroxide, continue stirring for 50-80 min, and cool to room temperature. Then add acryloyl chloride in a molar amount of 1.0-1.05 times that of the intermediate to the resulting mixture, mix well, and then add a mixture in a volume of 1.5-2.0 times that of dimethyl sulfoxide. Keep the mixture at 45-50℃ for 10-12 h to obtain the modifier.

[0018] Furthermore, the mixture is prepared by combining an aqueous sodium hydroxide solution and dimethyl sulfoxide in a volume ratio of 1:2, and the concentration of the aqueous sodium hydroxide solution is 25-30 wt%.

[0019] Furthermore, the specific composition of the antioxidant solution is as follows: 2.5-4 g / L glucose, 1-2 g / L benzotriazole, 0.8-2.5 g / L silane coupling agent, with the balance being deionized water, and its pH value is 2-4, and the current is 1.5-2.5 A.

[0020] Furthermore, the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-glycidyl etheroxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] 1. This invention involves reacting dodecanoic acid with 1,2-diaminobenzene in xylene at high temperature to generate an intermediate containing a benzimidazole ring. The intermediate is then reacted with epichlorohydrin under alkaline conditions to open the ring, followed by interaction with acryloyl chloride to introduce carbon-carbon double bonds, long-chain alkyl groups, and benzimidazole structures capable of photografting, thus obtaining the intermediate. A modifier is then prepared from the intermediate, epichlorohydrin, and acryloyl chloride as raw materials through a chemical reaction. Under a nitrogen atmosphere, mercaptopolyethylene glycol amino groups are dispersed in ethanol, and an initiator and modifier are added. Under the initiator and ultraviolet light irradiation, the modifier undergoes a mercapto-olefin click chemical reaction with the mercaptopolyethylene glycol amino groups, causing the modifier to covalently graft onto the segments of the mercaptopolyethylene glycol amino groups, ultimately yielding an effective additive.

[0023] The thiol groups in the prepared functional additives can form strong chemical adsorption with the copper surface, and the benzimidazole ring has a planar conjugated structure that can spread on the copper surface to inhibit dendrite growth. The polyethylene glycol segments provide steric hindrance and regulate the copper ion deposition rate. The grafted long-chain alkyl groups give the deposited layer certain lubrication and flexibility, reduce internal stress, and promote the formation of a dense, low-defect, and high-toughness grain structure in the copper foil. This results in the copper foil products having excellent bending resistance, meeting the stringent requirements of high-safety lithium batteries for the negative electrode current collector.

[0024] 2. This invention, by controlling the electrolyte composition and electrodeposition conditions, and combining the use of additives and antioxidant treatment, produces copper foil with excellent bending resistance and high safety. The additives, including bis(benzenesulfonyl)imide, gelatin, polyethylene glycol, dextrin, 3,4-dioxanebenzaldehyde, and sodium 3-mercapto-1-propanesulfonate, work synergistically to refine grains, smooth the surface, and reduce internal stress; in particular, the added functional additives further enhance the flexibility and fatigue fracture resistance of the copper foil. The antioxidant solution, containing glucose, benzotriazole, and a silane coupling agent, forms a dense protective film on the copper foil surface, preventing oxidation and discoloration, while simultaneously improving the bonding strength with the active material of the lithium battery negative electrode. Ultimately, the produced copper foil product not only possesses excellent flexibility and bending resistance but also excellent antioxidant properties.

[0025] The copper foil produced by this invention can effectively suppress electrode breakage and active material shedding during the charging and discharging process in lithium battery applications, thereby improving the cycle life and structural stability of the battery. At the same time, the anti-oxidation treatment enhances the corrosion resistance of the copper foil surface and its bonding force with the negative electrode material, thereby improving the overall safety and rate performance of the battery. Detailed Implementation

[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] The thiol-based polyethylene glycol amino (SH-PEG-NH2) used in Examples 1-3 and the comparative examples below was purchased from Shanghai Pengsheng Biotechnology Co., Ltd.

[0028] Example 1

[0029] A manufacturing process for bend-resistant copper foil for high-safety lithium batteries includes the following steps:

[0030] Step 1: Add copper wire with a purity ≥ 99.99% to a copper dissolving tank, add water and dilute sulfuric acid, and bubble air in to dissolve the copper. After adjusting the copper ion content, sulfuric acid concentration, chloride ion content, and temperature in the solution, an electrolyte is prepared. The electrolyte contains 90 g / L copper ions, 100 g / L H2SO4, and 20 ppm chloride ions, and the temperature of the electrolyte is set to 45℃.

[0031] Step 2: The electrolyte obtained in Step 1 is transferred to a high-level tank, and an additive is added to the high-level tank at a rate of 4 L / h. After mixing evenly, the electrolyte containing the additive is transferred through the inlet pipe of the foil-making machine to the electrolytic cell for electrodeposition to obtain green foil. The amount of additive used per cubic meter of electrolyte is 0.3 L. The electrodeposition temperature is set to 45℃, and the current density is set to 60 A / dm³. 2 The electrolyte flow rate is set to 35m³. 3 / h;

[0032] Step 3: The obtained raw foil is acid-washed with electrolyte and rinsed with pure water, then dried. The cleaned copper foil is then immersed in an antioxidant solution at 30°C for 20 seconds, and then successively squeezed dry by extrusion rollers, dried, wound up and slit to obtain a high-safety, bend-resistant copper foil for lithium batteries with a thickness of 5μm. The drying temperature is 120°C. The specific composition of the antioxidant solution is as follows: 2.5g / L glucose, 1g / L benzotriazole, 0.8g / L 3-aminopropyltriethoxysilane, with the balance being deionized water, and its pH value is 2. The current is 1.5A.

[0033] The specific composition of the additive is as follows: 0.5 g / L of bis(benzenesulfonyl)imide, 6 g / L of gelatin, 0.2 g / L of polyethylene glycol, 2 g / L of functional additive, 0.5 g / L of dextrin, 2 g / L of 3,4-dioxanebenzaldehyde, and 2 g / L of sodium 3-mercapto-1-propanesulfonate; and the molecular weight of the gelatin is 10,000; the molecular weight of the polyethylene glycol is 3,000.

[0034] The preparation method of the functional additive is as follows: Under a nitrogen atmosphere, mercaptopolyethylene glycol amino is uniformly dispersed in ethanol, heated to 60°C, and then an initiator and a modifier with a mass of 0.5 times that of mercaptopolyethylene glycol amino are added. The mixture is then heated at 40°C and under a light intensity of 80 mw / cm². 2 Under certain conditions, the mixture was irradiated with ultraviolet light at a wavelength of 365 nm for 3 hours, and then the ethanol was distilled off under reduced pressure to obtain the efficacy additive. The initiator was azobisisobutyronitrile, and its amount was 1 wt% of the total mass of mercaptopolyethylene glycol amino and modifier.

[0035] The preparation method of the modifier is as follows:

[0036] Step 1: Under nitrogen protection, dodecanoic acid, 1,2-diaminobenzene and xylene are mixed in a ratio of 1 mol: 1 mol: 2 L. The mixture is first kept at 155 °C for 6 h, and then at 215 °C for 4 h. The reaction solution is then cooled and distilled under reduced pressure. The resulting intermediate is stored for later use.

[0037] Step 2: At 55℃, the intermediate is added to dimethyl sulfoxide at a dosage ratio of 4 mol / L, and sodium hydroxide with an equimolar amount equal to that of dodecanoic acid is added. The mixture is stirred at 200 r / min for 60 min, and then epichlorohydrin with an equimolar amount equal to that of sodium hydroxide is added. The mixture is stirred for another 50 min and then cooled to room temperature. Acryloyl chloride with an equimolar amount equal to that of the intermediate is added to the resulting mixture. After mixing, a mixture with a volume of 1.5 times that of dimethyl sulfoxide is added. The mixture is kept at 45℃ for 12 h to obtain the modifier. The mixture is composed of sodium hydroxide aqueous solution and dimethyl sulfoxide in a volume ratio of 1:2, and the concentration of the sodium hydroxide aqueous solution is 25 wt%.

[0038] Example 2

[0039] A manufacturing process for bend-resistant copper foil for high-safety lithium batteries includes the following steps:

[0040] Step 1: Add copper wire with a purity ≥ 99.99% to a copper dissolving tank, add water and dilute sulfuric acid, and bubble air in to dissolve the copper. After adjusting the copper ion content, sulfuric acid concentration, chloride ion content, and temperature in the solution, an electrolyte is prepared. The electrolyte contains 100 g / L copper ions, 120 g / L H2SO4, and 25 ppm chloride ions, and the temperature of the electrolyte is set to 50℃.

[0041] Step 2: The electrolyte obtained in Step 1 is transferred to a high-level tank, and an additive is added to the high-level tank at a rate of 5 L / h. After mixing evenly, the electrolyte containing the additive is transferred through the inlet pipe of the foil-making machine to the electrolytic cell for electrodeposition to obtain green foil. The amount of additive used per cubic meter of electrolyte is 0.4 L. The electrodeposition temperature is set to 55℃, and the current density is set to 70 A / dm³. 2 The electrolyte flow rate is set to 40m³ / h. 3 / h;

[0042] Step 3: The obtained raw foil is acid-washed with electrolyte and rinsed with pure water, then dried. The cleaned copper foil is then immersed in an antioxidant solution at 35°C for 15 seconds, and then successively squeezed dry by extrusion rollers, dried, wound up and slit to obtain a high-safety, bend-resistant copper foil for lithium batteries with a thickness of 6μm. The drying temperature is 120°C. The specific composition of the antioxidant solution is as follows: 3g / L glucose, 1.5g / L benzotriazole, 1.5g / L 3-glycidyl etheroxypropyltrimethoxysilane, with the balance being deionized water, and its pH value is 3. The current is 2.0A.

[0043] The specific composition of the additive is as follows: 0.8 g / L of bis(benzenesulfonyl)imide, 8 g / L of gelatin, 0.3 g / L of polyethylene glycol, 3 g / L of functional additive, 0.6 g / L of dextrin, 3 g / L of 3,4-dioxomethylenebenzaldehyde, and 4 g / L of sodium 3-mercapto-1-propanesulfonate; the molecular weight of the gelatin is 15,000; and the molecular weight of the polyethylene glycol is 4,000.

[0044] The preparation method of the functional additive is as follows: Under a nitrogen atmosphere, mercaptopolyethylene glycol amino is uniformly dispersed in ethanol, heated to 65°C, and then an initiator and a modifier with a mass of 0.6 times that of mercaptopolyethylene glycol amino are added. The mixture is then heated at 45°C and under a light intensity of 100 mw / cm². 2 Under certain conditions, the mixture was irradiated with ultraviolet light at a wavelength of 365 nm for 3 hours, and then the ethanol was distilled off under reduced pressure to obtain the efficacy additive. The initiator was azobisisobutyronitrile, and its amount was 3 wt% of the total mass of mercaptopolyethylene glycol amino and modifier.

[0045] The preparation method of the modifier is as follows: Step 1: Under nitrogen protection, dodecanoic acid, 1,2-diaminobenzene and xylene are mixed at a ratio of 1 mol: 1.2 mol: 4 L. The mixture is first kept at 160 °C for 5 h, and then at 220 °C for 4 h. The reaction solution is then cooled and distilled under reduced pressure. The resulting intermediate is stored for later use. Step 2: At 60℃, the intermediate is added to dimethyl sulfoxide at a dosage ratio of 3 mol / L, and sodium hydroxide with an equimolar amount of dodecanoic acid is added. The mixture is stirred at 300 r / min for 50 min, and then epichlorohydrin with an equimolar amount of sodium hydroxide is added. The mixture is stirred for another 60 min and then cooled to room temperature. Acryloyl chloride with a molar amount of 1.03 times that of the intermediate is added to the resulting mixture. After mixing, a mixture with a volume of 2.0 times that of dimethyl sulfoxide is added. The mixture is kept at 50℃ for 12 h to obtain the modifier. The mixture is composed of sodium hydroxide aqueous solution and dimethyl sulfoxide in a volume ratio of 1:2, and the concentration of the sodium hydroxide aqueous solution is 30 wt%.

[0046] Example 3

[0047] A manufacturing process for bend-resistant copper foil for high-safety lithium batteries includes the following steps:

[0048] Step 1: Add copper wire with a purity ≥ 99.99% to a copper dissolving tank, add water and dilute sulfuric acid, and bubble air in to dissolve the copper. After adjusting the copper ion content, sulfuric acid concentration, chloride ion content, and temperature in the solution, an electrolyte is prepared. The electrolyte contains 120 g / L copper ions, 130 g / L H2SO4, and 30 ppm chloride ions, and the temperature of the electrolyte is set to 55℃.

[0049] Step 2: The electrolyte obtained in Step 1 is transferred to a high-level tank, and an additive is added to the high-level tank at a rate of 6 L / h. After mixing evenly, the electrolyte containing the additive is transferred to the electrolytic cell through the inlet pipe of the foil-making machine for electrodeposition to obtain green foil. The amount of additive used per cubic meter of electrolyte is 0.6 L. The electrodeposition temperature is set to 65℃, and the current density is set to 80 A / dm³. 2 The electrolyte flow rate is set to 45m³ / h. 3 / h;

[0050] Step 3: The obtained raw foil is acid-washed with electrolyte and rinsed with pure water, then dried. The cleaned copper foil is then immersed in an antioxidant solution at 40°C for 10 seconds, and then successively squeezed dry by extrusion rollers, dried, wound up and slit to obtain a high-safety, bend-resistant copper foil for lithium batteries with a thickness of 8μm. The drying temperature is 130°C. The specific composition of the antioxidant solution is as follows: 4g / L glucose, 2g / L benzotriazole, 2.5g / L γ-mercaptopropyltrimethoxysilane, with the balance being deionized water, and its pH value is 4. The current is 2.5A.

[0051] The specific composition of the additive is as follows: 1.0 g / L of bis(benzenesulfonyl)imide, 10 g / L of gelatin, 0.3 g / L of polyethylene glycol, 5 g / L of functional additive, 0.8 g / L of dextrin, 5 g / L of 3,4-dioxanebenzaldehyde, and 5 g / L of sodium 3-mercapto-1-propanesulfonate; and the molecular weight of the gelatin is 20,000; the molecular weight of the polyethylene glycol is 5,000.

[0052] The preparation method of the functional additive is as follows: Under a nitrogen atmosphere, mercaptopolyethylene glycol amino is uniformly dispersed in ethanol, heated to 70°C, and then an initiator and a modifier with a mass of 0.7 times that of mercaptopolyethylene glycol amino are added. The mixture is then heated at 50°C and under a light intensity of 120 mw / cm². 2 Under certain conditions, the mixture was irradiated with ultraviolet light at a wavelength of 365 nm for 2 hours, and then the ethanol was distilled off under reduced pressure to obtain the functional additive.

[0053] The initiator is azobisisoheptanenitrile, and its amount is 5 wt% of the total mass of mercaptopolyethylene glycol amino and modifier.

[0054] The preparation method of the modifier is as follows:

[0055] Step 1: Under nitrogen protection, dodecanoic acid, 1,2-diaminobenzene and xylene are mixed at a ratio of 1 mol: 1.5 mol: 5 L. The mixture is first kept at 160 °C for 4 h, and then at 220 °C for 3 h. The reaction solution is then cooled and distilled under reduced pressure. The resulting intermediate is stored for later use.

[0056] Step 2: At 60℃, the intermediate is added to dimethyl sulfoxide at a dosage ratio of 2 mol / L, and sodium hydroxide with an equimolar amount of dodecanoic acid is added. The mixture is stirred at 400 r / min for 40 min, and then epichlorohydrin with an equimolar amount of sodium hydroxide is added. The mixture is stirred for another 80 min and then cooled to room temperature. Acryloyl chloride with a molar amount of 1.05 times that of the intermediate is added to the resulting mixture. After mixing, a mixture with a volume of 2.0 times that of dimethyl sulfoxide is added. The mixture is kept at 50℃ for 10 h to obtain the modifier. The mixture is composed of sodium hydroxide aqueous solution and dimethyl sulfoxide in a volume ratio of 1:2, and the concentration of the sodium hydroxide aqueous solution is 30 wt%.

[0057] Comparative Example: The difference from Example 1 is that the additives used in this comparative example do not contain efficacy additives.

[0058] Performance testing: The relevant properties of the copper foil samples produced in Examples 1-3 and the comparative examples were tested respectively, and the test data are recorded in the table below:

[0059]

[0060] By comparing and analyzing the relevant data in the table, it can be seen that the copper foil produced by this invention possesses excellent bending resistance, high elongation, and oxidation resistance, effectively suppressing electrode breakage and active material shedding during the charging and discharging process of lithium batteries, and significantly improving the cycle life and safety of the battery. This indicates that the production process of the high-safety, bend-resistant copper foil for lithium batteries provided by this invention has a broader market prospect and is more suitable for widespread application.

[0061] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0062] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A manufacturing process for bend-resistant copper foil for high-safety lithium batteries, characterized in that, Includes the following steps: Step 1: Add copper wire with a purity of ≥99.99% to a copper dissolving tank, add water and dilute sulfuric acid, and bubble air in to dissolve the copper. After adjusting the copper ion content, sulfuric acid concentration, chloride ion content and temperature in the solution, an electrolyte is obtained. Step 2: The electrolyte obtained in Step 1 is transported to a high-level tank, and additives are added to the high-level tank at a dosage ratio of 4-6 L / h. After mixing evenly, the electrolyte containing additives is transported to the electrolytic cell through the inlet pipe of the foil-making machine for electrodeposition to obtain the foil. The dosage of additives in each cubic meter of electrolyte is 0.3-0.6 L. Step 3: The obtained raw foil is acid-washed with electrolyte and rinsed with pure water, then dried. The cleaned copper foil is then immersed in an antioxidant solution at 30-40℃ for 10-20 seconds. It is then squeezed dry by extrusion rollers, dried, wound up and slit to obtain a high-safety, bend-resistant copper foil for lithium batteries with a thickness of 5-8μm. The drying temperature is 120-130℃.

2. The manufacturing process of a high-safety, bend-resistant copper foil for lithium batteries according to claim 1, characterized in that: The electrolyte contains 90-120 g / L copper ions, 100-130 g / L H2SO4, and 20-30 ppm chloride ions, and the electrolyte temperature is set to 45-55℃.

3. The manufacturing process of a high-safety lithium battery bend-resistant copper foil according to claim 1, characterized in that: The electrodeposition temperature was set to 45-65℃, and the current density was set to 60-80 A / dm³. 2 The electrolyte flow rate is set to 35-45 m³ / h. 3 / h.

4. The manufacturing process of a high-safety, bend-resistant copper foil for lithium batteries according to claim 1, characterized in that, The specific composition of the additive is as follows: 0.5-1.0 g / L of bis(benzenesulfonyl)imide, 6-10 g / L of gelatin, 0.2-0.3 g / L of polyethylene glycol, 2-5 g / L of functional additive, 0.5-0.8 g / L of dextrin, 2-5 g / L of 3,4-dioxomethylenebenzaldehyde, and 2-5 g / L of sodium 3-mercapto-1-propanesulfonate; and the molecular weight of the gelatin is 10,000-20,000; the molecular weight of the polyethylene glycol is 3,000-5,000.

5. The manufacturing process of a high-safety, bend-resistant copper foil for lithium batteries according to claim 1, characterized in that, The preparation method of the functional additive is as follows: under a nitrogen atmosphere, mercaptopolyethylene glycol amino is uniformly dispersed in ethanol, and after heating to 60-70℃, an initiator and a modifier with a mass of 0.5-0.7 times that of mercaptopolyethylene glycol amino are added. The mixture is then subjected to a temperature of 40-50℃ and a light intensity of 80-120 mw / cm². 2 Under certain conditions, the mixture is irradiated with ultraviolet light at a wavelength of 365nm for 2-3 hours, and then the ethanol is distilled off under reduced pressure to obtain the functional additive.

6. The manufacturing process of a high-safety lithium battery bend-resistant copper foil according to claim 5, characterized in that: The initiator is any one of azobisisoheptanenitrile, azobisisobutyronitrile, and dimethyl azobisisobutyrate, and its amount is 1-5 wt% of the total mass of mercaptopolyethylene glycol amino and modifier.

7. The manufacturing process of a high-safety, bend-resistant copper foil for lithium batteries according to claim 5, characterized in that, The method for preparing the modifier is as follows: Step 1: Under nitrogen protection, dodecanoic acid, 1,2-diaminobenzene and xylene are mixed at a ratio of 1 mol:(1-1.5) mol:2-5 L. The mixture is first kept at 155-160℃ for 4-6 h, and then at 215-220℃ for 3-4 h. The reaction solution is then cooled and distilled under reduced pressure. The resulting intermediate is stored for later use. Step 2: At 55-60℃, add the intermediate to dimethyl sulfoxide at a dosage ratio of 2-4 mol / L, and add sodium hydroxide in an equimolar amount with dodecanoic acid. Mix and stir at a speed of 200-400 r / min for 40-60 min, then add epichlorohydrin in an equimolar amount with sodium hydroxide, continue stirring for 50-80 min, and cool to room temperature. Then add acryloyl chloride in a molar amount of 1.0-1.05 times that of the intermediate to the resulting mixture, mix well, and then add a mixture in a volume of 1.5-2.0 times that of dimethyl sulfoxide. Keep the mixture at 45-50℃ for 10-12 h to obtain the modifier.

8. The manufacturing process of a high-safety lithium battery bend-resistant copper foil according to claim 7, characterized in that: The mixture is prepared by combining sodium hydroxide aqueous solution and dimethyl sulfoxide in a volume ratio of 1:2, and the concentration of sodium hydroxide aqueous solution is 25-30 wt%.

9. The manufacturing process of a high-safety, bend-resistant copper foil for lithium batteries according to claim 1, characterized in that, The specific composition of the antioxidant solution is as follows: 2.5-4 g / L glucose, 1-2 g / L benzotriazole, 0.8-2.5 g / L silane coupling agent, with the balance being deionized water, and its pH value is 2-4, and the current is 1.5-2.5 A.

10. The manufacturing process of a high-safety lithium battery bend-resistant copper foil according to claim 9, characterized in that: The silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-glycidyl etheroxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.